Hope in the context of suffering and injustice: A contextual pastoral response based on 1 Peter 1:13–25 - du Plessis, Amanda L. (Verbum et ecclesia, 2025)
First and second Peter are often studied as general texts in New Testament scholarship, yet their pastoral value becomes evident when counsellors consider the message of living hope in the midst of suffering and injustice. This article provides an overview of the different components of emotions, the theology and context of suffering, as well as a theological foundation for nurturing hope. It further explores the practical implications of hope in 1 Peter, offering a contextual pastoral response for times of hardship. Intradisciplinary and/or interdisciplinary implications: This article also draws lessons from Brazilian educator Paulo Freire (1921–1997) and Holocaust survivor Viktor Frankl (1905–1997) on their experiences of suffering and injustice, highlighting insights relevant to pastoral counselling. The goal is to encourage believers to focus their hope on God’s grace and to live a righteous life amid suffering, reflecting the summonses made in the Peter letters.